WILD TURKEY PRODUCTION, FALL AND SPRING HARVEST INTERACTIONS, AND RESPONSES TO HARVEST MANAGEMENT IN PENNSYLVANIA - Gerald A. Wunz; Anthony S. Ross (Wildlife Society Bulletin)
Abstract: Relationships between wild turkey (Meleagris gallopavo silvestris) production, spring and fall harvest, and management strategies to control fall harvest were evaluated. We examined 14 years of brood counts, and harvest information from postal questionnaires and from hunter report cards. Brood counts were more highly correlated with hunter report cards than with the postal survey. An inverse relationship between spring and fall harvests from the postal survey indicate a reduction in fall harvests may result in greater spring harvests. After a management area concept was adopted for setting fall hunting season length, based on the results of the previous summer's brood counts, fall harvest trends have closely correlated with those of the brood counts. A correlation between brood counts and annual harvest on one of the management regions, indicated these brood counts were also a valid index to turkey abundance and precursors of harvest on a regional basis. Longer fall seasons were negatively correlated with the following summer's brood counts. Poult:hen ratios were poor indicators of overall production. Brood counts of hens and poults are a reliable index of turkey population trends in Pennsylvania.